Understanding the Palm Oil Utilization Preference: A Literature Review and Preference Measurement - Lucky Adhitiya; Rifelly Dewi Astuti (Institut Teknologi Sepuluh Nopember, 2019)
Energy supply security has become the world’s issue this past decades. World’s energy demand keep growing yet supply remains stable. Numerous renewable energy sources are developed to fulfil this energy supply gap. This issue is also being a concern in Indonesia. Palm oil is considered as one of the renewable energy because of its production flexibility. Palm oil could be processed into cooking oil and fuel energy such as biodiesel. Objective of this present study is to understand the palm oil utilization preference either as the cooking oil or biodiesel. Literature review is conducted to explore variables that is being considered as preference variable. This present study conducted review in several literature that were published ranged from 2010 to 2018. Three variables were considered as a result of literature review. The first variable is sustainability aspect which represent life cycle of the processed product. The second variable is policy which could influence the industry’s stakeholder to conduct a utilization decision. The last variable is emission that is being produced by the processed product. This present study also conducted preference measurement in order to measure the preference of palm oil utilization either as he cooking oil or biodiesel. As the result, a research map is proposed for the future research direction